Breeding Performance of Catla, Catla catla (Ham.) Fed with Different Formulated Diets - J.K., Manissery; K., Venkateshmurthy; B., Gangadhara; M.C., Nandeesha (Fishery Technology, 2025)
Breeding performance of catla, (Catla catla) was assessed through feeding trial for three months. Test diets with 30% protein (diet B) and 35% protein (diet C) were developed using a combination of rice bran, groundnut cake and fish meal. The proportion of these ingredients was reduced in diet D and replaced with horse gram, black gram, broken cake, rice and maize. Control diet (diet A) having 25% protein was formulated with 1:1 mixture of rice bran and groundnut oil. The breeding weight loss in females was lower (P